El camino a casa / Zhang Yimou - Yimou, Zhang (Madrid Sony pictures, 2012)
Prompted by the death of his father and the grief of his mother, a man recalls the story of how they met in flashback.
Idiomas : Español, Mandarín, Italiano. subt.: Español, inglés, italiano, portugués
Ziyi Zhang, Honglei Sun, Hao Zheng
Apta para todos los públicos
Keywords: Películas cinematográficas -- DVD